Kinetics and adsorption in the electrochemical reduction of aromatic ketones . - Rudd, Eric James. (University of Ottawa (Canada), 1969)
In the study of organic electrode processes it is desirable to complement kinetic and polarographic information by direct adsorption studies in relation to data on reaction orders and Tafel slopes. The electro-reduction of acetophenone in acidic media (pH < 3) has been shown to yield only 2,3-diphenylbutane-2,3-diol (acetophenone pinacol) with a high coulombic efficiency. Furthermore, the electrode reaction occurs at cathodic potentials sufficiently removed from those at which currents attributed to the evolution of hydrogen are significant, so that in the potential range studied, only a single Faradaic process occurred. This electrochemical reaction has therefore been studied in relation to (a) the adsorption and orientation of the ketone at the mercury electrode surface, (b) the kinetic behaviour of the electrode reaction, and (c) the adsorption of the pinacol and its effect, if any, upon the kinetics of the electrode process. Studies of the electrode kinetics comprised both potentiostatic steady-state and potentiodynamic non-steady state measurements employing a "triangular" potential sweep and a potential step procedure. Limiting current behaviour was consistently observed in the steady-state measurements and was attributed to the overall rate of reaction being determined ultimately by the rate of diffusion of the ketone to the electrode surface. This conclusion was supported by the results of the analysis of current-potential curves obtained from potentiodynamic studies. A potentiostatic "potential step" technique was introduced as a complementary method of study in an effort to obtain current-potential relations at very short time intervals after the electrode potential had been established. However, oscillatory behaviour of the current was observed for a few milliseconds after the application of the potential step and this effect limited the value of this method in the study of the electrode process. The electrochemical reaction was shown to be sensitive to the composition of the aqueous-organic solvent (experiments were conducted in methanol-sulphuric acid and in methanol-water-sulphuric acid mixtures) and to the concentration of hydrogen ions in the solution. However, the absence of a significant H/D primary isotope effect indicated that the proton was not critically involved in the rate-determining step. (Abstract shortened by UMI.)
Keywords: Chemistry, Organic.